Adrenal myelolipoma: a case report (BIRDEM Medical Journal, 2021)
Myelolipoma is a relatively rare benign tumor of adrenal gland. Most cases are non-functioning and asymptomatic and usually discovered during various diagnostic-imaging procedures performed for other diseases of abdomen. Cases associated with excessive hormone secretion have been reported which may constitute adrenocortical adenomas with associated myelolipomatous components. Histopathological findings are very interesting and the tumor is composed of bone marrow elements with various amounts of fatty tissue. The fat component in myelolipoma can facilitate the diagnosis by radiological examination. Here, we report a case of adrenal myelolipoma and its clinical presentation and evaluation. In this case, initially the patient presented with nonspecific abdominal symptoms. Her adrenal tumor was found incidentally and the final diagnosis was proved by histopathology.BIRDEM Med J 2021; 11(3): 231-234